RANCANG BANGUN WEBSITE TAS BERBASIS RECOMMENDED SYSTEM DENGAN MENGGUNKAN METODE ITEM BASED COLLABORATIVE FILTERING PADA UKM REVIORA - Agus Salim; Shah Khadafi (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2022)
ABSTRACTIn general, almost all people necessitate bags for bringing their documents, precious items, or only just for supplementary. Since the demand for bags gets increasing, they become the recent trend mostly favored by people. They are very interested in numerous models, colors, and shapes of bags. Therefore, companies producing bags must be able to give solutions to users so that they know the types of bags which must be produced and sold massively. A system of recommendation will be very beneficial to give suggestions to business owners or users to ensure them about bag types that should be reproduced. For this reason, the researcher developed a recommendation system using a Collaborative Filtering method. After carrying out surveys on products and users as well as conducting trials or system tests, this research obtained MSE (Mean Squared Error) 1.66.